The climate-biodiversity-health nexus: a framework for integrated community sustainability planning in the Anthropocene - Newell, Robert (Frontiers in Climate, 2023)
Integrated approaches to planning and policy are important for making progress toward sustainability. A variety of other frameworks have been developed for facilitating such approaches to planning and policy, such as the water-energy-food (WEF) nexus. However, the WEF nexus has been critiqued for a lack of clarity in how to apply the framework, whereas a goals-oriented framework potentially could be more easily applied and operationalized. This paper proposes such a framework, referred to here as the climate-biodiversity-health (CBH) nexus. The paper details the features of the CBH nexus framework, the interactions among its domains, and its potential applications. The CBH nexus consists of three domains (i.e., climate action, biodiversity conservation, and community health) and six subdomains (i.e., climate change mitigation, climate change adaptation, habitat protection, wildlife health, physical health, and mental health). The framework can be applied in planning practice to develop checklists/toolkits for guiding new plans and developments, and it can also be applied in community-based research as a lens for participatory modelling exercises. Continued experimentation with, and improvement of, the CBH framework will reveal its most useful applications, thereby opening new opportunities for communities to effectively develop and implement integrated sustainability plans and policies.